2006
DOI: 10.1002/clc.4960290109
|View full text |Cite
|
Sign up to set email alerts
|

Effect of statins and white blood cell count on mortality in patients with ischemic left ventricular dysfunction undergoing percutaneous coronary intervention

Abstract: SummaryBackground: While morbidity and mortality were shown to be increased in the setting of an elevated white blood cell (WBC) count for patients with acute coronary syndrome, the impact of statin therapy on mortality for patients with an elevated WBC count is unknown in high-risk patients with coronary artery disease.Hypothesis: The goal of this study was to determine whether statin therapy improved survival in patients with elevated WBC count undergoing percutaneous coronary intervention (PCI) with preexis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
3
0

Year Published

2007
2007
2015
2015

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 23 publications
(33 reference statements)
1
3
0
Order By: Relevance
“…In the present meta-analysis, approach-related bleeding events represented only about 1% when compared to an overall rate of 7%. When compared to large randomized controlled trials comparing radial versus femoral access in STEMI patients [ 34 36 ], the lower incidence of access-related bleeding is confirmed, while in the present paper an overall higher rate of hemorrhages is present, probably due to inclusion also of NSTEMI patients, who usually present with higher rates of comorbidity [ 1 , 3 , 4 ]. It is important to note that CRUSADE was the only score externally validated in NSTEMI patients, while the other two were tested for all myocardial infarction or only STEMI.…”
Section: Discussionsupporting
confidence: 68%
“…In the present meta-analysis, approach-related bleeding events represented only about 1% when compared to an overall rate of 7%. When compared to large randomized controlled trials comparing radial versus femoral access in STEMI patients [ 34 36 ], the lower incidence of access-related bleeding is confirmed, while in the present paper an overall higher rate of hemorrhages is present, probably due to inclusion also of NSTEMI patients, who usually present with higher rates of comorbidity [ 1 , 3 , 4 ]. It is important to note that CRUSADE was the only score externally validated in NSTEMI patients, while the other two were tested for all myocardial infarction or only STEMI.…”
Section: Discussionsupporting
confidence: 68%
“…Nonetheless, as CD19, CD20, CD27, and CD43 positive B cells spontaneously produces IgM, further study is required to determine if these cells produce NAb to OSE, determine if numbers of circulating CD19, CD20, CD27, and CD43 positive B cells are associated with circulating levels of NAb to OSE and atherosclerosis. It has been well established that leukocytosis is independently associated with CAD [63] and poor outcomes after cardiovascular events [6466] suggesting that circulating leukocyte counts can act as biomarkers for disease progression and outcome. Though less established, it has been shown that circulating lymphocyte counts show an inverse relationship to recurrent ischemic events and cardiovascular mortality [63].…”
Section: B Cells In Human Vascular Diseasementioning
confidence: 99%
“…Lipinski et al [19] studied patients with poor left ventricular function and evaluated the relationship between statins and white blood cell counts. The investigators could predict the patients who would benefit from the statin in terms of late outcome based on those who had higher white counts, suggesting more inflammation at the time of the procedure.…”
Section: Special Subgroupsmentioning
confidence: 99%